Size distribution and sex ratio in the spider crab Epialtus brasiliensis (Dana 1852) associated with seaweed on a rocky shore in southeastern Brazil (Crustacea, Decapoda, Brachyura, Majoidea, Epialtidae). - Teixeira, Gustavo Monteiro; Fransozo, Vivian; Castilho, Antonio Leao; da Costa, Rogerio Caetano; de Morais Freire, Fulvio Aurelio (My University, 2008)
This study analyzed a population of the spider crab Epialtus brasiliensis, in regard to its size distribution, sex ratio and Sexual maturity. The study was conducted on a rocky shore in the Ubatuba region, state of Silo Paulo, Brazil, where a wide strip of algae covers the intertidal zone. A total of 378 specimens were obtained: 200 males (128 juvenile and 72 adult crabs) and 178 females (46 juveniles and 132 adults). Their Sizes ranged from 3.4 to 16.7 mm carapace length (CL). Taking into account that the pubertal and terminal molts are coincident in majid crabs, the maximum sizes attained by males and females are especially dependent on the factors that influence sexual maturity, mainly food resources, temperature and intraspecific competition. Males of E. brasiliensis occurred in all size classes, whereas females occurred only as far the 10th size class (12-13 min CL). file total sex ratio did not differ statistically from 1 : 1, but when the juvenile and adult specimens were analyzed separately the differences between sexes were significantly different, with higher proportions of immature males and mature females. The CL50 calculated for males and females was 10.4, and 6.9 min CL, respectively. Thus, males reach their sexual maturity at a larger size than females. This feature may be important for the reproductive strategy of this species, because larger males probably have greater reproductive Success.